Qualidade de vida em saúde e bem-estar subjetivo em idosos : um estudo de base populacional - Lima, Margareth Guimarães, 1968- (2012)
Orientadores: Marilisa Berti de Azevedo Barros, Maria Cecilia Goi Porto Alves